2017
DOI: 10.1177/016146811711900704
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Determinants of Chronic Absenteeism: A Bioecological Systems Approach

Abstract: Background/Context Chronic school absenteeism is a pervasive problem across the US; in early education, it is most rampant in kindergarten and its consequences are particularly detrimental, often leading to poorer academic, behavioral and developmental outcomes later in life. Though prior empirical research has identified a broad range of determinants of chronic absenteeism, there lacks a single, unified theoretically driven investigation examining how such factors concurrently explain the incidence of chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 45 publications
(79 reference statements)
1
39
0
Order By: Relevance
“…Only a small proportion of papers in our review discussed potential mechanisms in their literature reviews (Darmody et al ., 2008; Hunt & Hopko, 2009; Nolan et al ., 2013; Gottfried, 2014; Morrissey et al ., 2014; Gottfried & Gee, 2017; Lim et al ., 2019). Even among studies whose primary goal was to investigate the association between SES and school absenteeism, only a quarter provided some theoretical considerations on how SES affects school absence risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a small proportion of papers in our review discussed potential mechanisms in their literature reviews (Darmody et al ., 2008; Hunt & Hopko, 2009; Nolan et al ., 2013; Gottfried, 2014; Morrissey et al ., 2014; Gottfried & Gee, 2017; Lim et al ., 2019). Even among studies whose primary goal was to investigate the association between SES and school absenteeism, only a quarter provided some theoretical considerations on how SES affects school absence risk.…”
Section: Resultsmentioning
confidence: 99%
“…An important risk antecedent of school absenteeism identified in several studies is family socioeconomic status (SES) (e.g., Gottfried & Gee, 2017; Gubbels et al ., 2019; Klein et al ., 2020). Students from lower SES backgrounds are over‐represented among those absent from school (e.g., Morrissey et al ., 2014; Gottfried & Gee, 2017; Gennetian et al ., 2018; Gubbels et al ., 2019). For instance, Garcia and Weiss (2018) found that 23.2% of students eligible for free and reduced‐price lunch (FRPL) missed three or more days of school per month compared to only 15.4% of those not eligible for FRPL.…”
Section: Introductionmentioning
confidence: 99%
“…Although associations between LTCs, mental health and absenteeism are well established, most research is cross sectional and the extent to which these difficulties persist is unknown. Furthermore, less is known about the relative impact of different types of LTC (Allison & Attisha, 2019; Gottfried & Gee, 2017), and the mental health and educational needs of CYP with different conditions may not be equal. This study investigates cross‐sectional and longitudinal associations of LTCs with mental health and school absenteeism.…”
Section: Introductionmentioning
confidence: 99%
“…Control variables were drawn from the kindergarten year and include: Child age, child gender (dummy coded, male = 1), child race/ethnicity (dummy coded so that White children were the referent group), home language (dummy coded so that children who spoke English at home were the referent group), parent years of education, parent work hours, parent marital status (dummy coded so that married parents were the referent group), income-to-needs-ratio, household size, number of children under 18 in the household, and parent age. In addition to these demographic covariates that prior studies suggest are correlated with children’s school absences (e.g., Gottfried & Gee, 2017), we also controlled for whether children attended a summer program focused on the transition to kindergarten (Bridge to Kindergarten; Duncan et al, 2018) along with parent engagement in kindergarten transition activities and parent home and school-based involvement. We adjusted for these additional indicators of parental engagement given evidence that children whose parents are more engaged in their education are less likely to be absent (Gottfried & Gee, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to these demographic covariates that prior studies suggest are correlated with children's school absences (e.g., Gottfried & Gee, 2017), we also controlled for whether children attended a summer program focused on the transition to kindergarten (Bridge to Kindergarten; Duncan et al, 2018) along with parent engagement in kindergarten transition activities and parent home and school-based involvement. We adjusted for these additional indicators of parental engagement given evidence that children whose parents are more engaged in their education are less likely to be absent (Gottfried & Gee, 2017). And because children were assessed between September and November (fall of kindergarten) and again between April and June (spring of kindergarten and first grade), all models also control for the time between assessments.…”
Section: Analytic Strategymentioning
confidence: 99%